Seasonal dynamics of flock interaction networks across a human-modified landscape in lowland Amazonian rain forest - Rutt, Cameron L.; Stouffer, Philip C. (Ecological Applications, 2020)
Although lowland tropical rain forests were once widely believed to be the archetype of stability, seasonal variation exists. In these environments, seasonality is defined by rainfall, leading to a predictable pattern of biotic and abiotic changes. Only the full annual cycle reveals niche breadth, yet most studies of tropical organisms ignore seasonality, thereby underestimating realized conditions. If human-modified habitats display more seasonal stress than intact habitats, then ignoring seasonality will have particularly important repercussions for conservation. We examined the seasonal dynamics of Amazonian mixed-species flocks, an important species interaction network, across three habitats with increasing human disturbance. We quantified seasonal space use, species richness and attendance, and four ecological network metrics for flocks in primary forest, small forest fragments, and regenerating secondary forest in central Amazonia. Our results indicate that, even in intact, lowland rain forest, mixed-species flocks exhibit seasonal differences. During the dry season, flocks included more species, generally ranged over larger areas, and displayed network structures that were less complex and less cohesive. We speculate that—because most flocking species nest during the dry season, a time of reduced arthropod abundance—flocks are simultaneously constrained by these two competing pressures. Moreover, these seasonal differences were most pronounced in forest fragments and secondary forest, habitats that are less buffered from the changing seasons. Our results suggest that seasonality influences the conservation value of human-modified habitats, raising important questions about how rain forest organisms will cope with an increasingly unstable climate. © 2020 by the Ecological Society of America
Keywords: Amazon; deforestation; ecological networks; forest fragmentation; mixed-species flocks; Neotropics; seasonality; species interaction networks